Confirmation of a continental-scale disjunction for the fern Campyloneurum decurrens (Polypodiaceae) - León, Blanca (2019)
We confirm the presence of Campyloneurum decurrens in the western side of South America based on herbarium collections. Specifically, we report three additional localities for its geographical range, two in Peru and one in Ecuador, and provide additional morphological information on this species. This report confirms a disjunction for this species between the Atlantic Forest in southeastern Brazil and the lowland forests in the Peruvian Amazon, and in the Ecuadorean Choco.